2010
DOI: 10.1111/j.1540-8159.2010.02975.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Cephalic Venous Access for Cardiac Resynchronization Device Implantation

Abstract: CRT devices can be implanted using cephalic access alone in a large majority of cases. This approach is safe and efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…The CV cutdown technique has no disadvantages of the AV/SV puncture approach, and is usually the primary choice of operators for introducing leads into the venous system [9,15]. Finally, the usefulness of the CV in terms of successful lead passage is determined by morpho-anatomical parameters of the vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CV cutdown technique has no disadvantages of the AV/SV puncture approach, and is usually the primary choice of operators for introducing leads into the venous system [9,15]. Finally, the usefulness of the CV in terms of successful lead passage is determined by morpho-anatomical parameters of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The CV cutdown technique performed in the deltopectoral triangle is typically the first and preferred attempt at venous access, as it is associated with a lower risk of traumatising the surrounding structures in comparison with the AV puncture approach [3,9,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is quite subjective and has not been systematically studied to date. In addition, there is no evidence that access to the heart for cardiac resynchronization with an ICD is facilitated by three smaller leads, since even the cephalic vein-guidewire technique can accommodate all three of the larger leads, one of which provides defibrillation capability [4][5][6]. Two studies have evaluated venous occlusion and have shown no relationship between lead size and incidence of occlusion [7,8].…”
Section: Advantages Of Small-diameter Leadsmentioning
confidence: 99%
“…The most commonly used techniques are the cephalic vein (CV) "cut-down" method and direct needle puncture of the subclavian vein (SV) or axillary vein (AV) (ie, the Seldinger technique). 3,5 The CV is located in the deltopectoral grove, penetrating the clavipectoral fascia to join the axillary vein medial to the pectoralis minor muscle and then together continuing as the subclavian vein. 2 Variations and anomalies of the CV may prolong the procedure time and result in unsuccessful cephalic access in up to 40% of patients, especially for less experienced operators.…”
Section: Introductionmentioning
confidence: 99%